Pengukuran Tingkat Pemahaman Konsep Fisika pada Materi Suhu dan Kalor - Said, Muhammad Amin; Ishaq (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to evaluate students' understanding of physics concepts related to temperature and heat at SMA Negeri 10 Gowa. The research employs a descriptive quantitative method, utilizing a closed two-tier multiple-choice diagnostic test as the research instrument. The analysis reveals that the XI MIA 2 students demonstrate a very high understanding in the aspect of translation, with an average score of 88.60. In contrast, the interpretation aspect is categorized as moderate, with an average score of 44.70. The extrapolation aspect shows a high understanding, with an average score of 72.70. Overall, students' understanding of physics concepts related to temperature and heat is categorized as high, with an average score of 65.88. These findings indicate that while there are areas needing improvement, many students have shown a solid understanding of the concepts taught. This research is expected to provide insights for developing more effective teaching methods.